Impact of Folic Acid and Cyanocobalamin on Growth, Milk Yield and its Components of Awassi Ewes and their Lambs - Mozhir K.K. Almahdawi (Journal of Global Pharma Technology, 2018)
The aim is to knowledge of vital role of folic acid and B12 vitamin on growth, milk production, milk components of Awassi sheep and their lambs.This experiment was carried out on 24 head of pregnant Awassi ewes with lambing of them in one of the private farms at Altagia village in southern of Hilla city. The experiment was included two phases, the first phase were dosage to Awassi ewes with two vitamins by mouth during experiment periods through estrus, gestation and parturition. The animals were randomly distributed into four treatments, the first treatment (control) without vitamins, second treatment was daily treated by 5mg/ewe of folic acid and third treatment was dosage of cyanocobalamin (B12 vitamin) with 225 μgm per ewe at twice time every week and fourth treatment were combination treated of folic acid and B12 vitamin as the same concentrations above. The second phase of the experiment, which began from birth of lambs and lasted weaning age ( 90 days).The lambs were dosage with two vitamins by mouth method after four hours of their born as the same mentioned of ewes in the first phase of experiment .The lambs were randomly distribution into four treatments, the first treatment was called control treatment without treated any vitamins and the second treatment were dosage with 1mg of folic acid to twice time per week, as well as the third treatment were treated with 125 μgm of B12 vitamin for twice time per week, As either fourth treatment the animals were mixture dosage of two vitamins (folic acid, cyanocobalmine) in the same concentrations. The results of statistical analysis of the first phase indicated the existence of significant differences (P≤0.05) on the averages of ewe’s weights at parturition and weaning, amount of daily feed intake, proportion of milk sugar, total protein and triglycerides of blood. As well as the results indicated high significant differences (P≤0.01) on the average of weights of ewes at the end of gestation, feed conversion , daily milk production , moisture, crude protein, crude fat non fats , total solids of milk and concentrations of cholesterol and albumin in blood of ewes. As for the second phase the results were shown significant differences (P≤0.05) on average amount of daily feed intake, total protein, albumin, triglycerides and cholesterol in the blood of lambs and another beside ,the results indicated high significant differences (P≤0.01) on average of live weight of lambs at birth and weaning, amount of daily feed intake and daily and total weight gains, and cholestrol concentration in the blood of Awassi lambs. We conclude that animals were dosages of folic acid with B12 vitamin were improving of health status and to improve significantly in most of traits of productive performance, growth and blood characteristics of ewes and their lambs as compared to the control treatment. Keywords: Folic acid, B12 vitamin, Milk yield, Milk components, Blood proteins.